Promotion of healthy lifestyles in early childhood: the perspectives of family members and experts - Duarte, Ana (2022)
Background: The importance of promoting healthy lifestyles in the first years of life is recognized. Identifying priority areas for intervention related to the promotion of healthy lifestyles is an urgent challenge. Objective: To explore the perspectives of family members and experts on priority areas for intervention related to the promotion of healthy lifestyles in early childhood. Methodology: Qualitative, exploratory, and descriptive study, using focus group sessions. Seven experts from the health, social, education, and media areas and three family members of young children participated in the study. Semi-structured interviews were conducted, and Bardin’s content analysis technique was used. Results: Two major priority areas emerged: determinants of diet and determinants of movement (physical activity, sedentary behavior, and sleep). Conclusion: The determinants of diet and movement are priority areas for intervention. The involvement of caregivers (e.g., parents, early childhood educators) is essential to promoting healthy lifestyles.